HOW TO PREVENT CRIMINALITY OR PRISONS–CONCENTRATION CAMPS FOR A CULTURE THAT HATES CHILDREN OR THE DRUG PROBLEM: TEN SUGGESTIONS FROM A PSYCHIATRIST IN PRISON - A. Nigro, Dr. Samuel (Journal of Medical Biomedical and Applied Sciences, 2019)
Drugs and crime are destroying America. There are over two million incarcerated young men and women (more than in the military). Almost all of their crimes are related to drug abuse beginning about 12 years of age. The epidemic of drug abuse at early ages is based on the failure of families, schools and the communication industry to immunize youths against the contagion of drug abuse and the related rage against our culture which created them. There is one drug abuse arrest every 20 seconds. The growing acceptance of marihuana seems counterproductive. Basically, people want to escape from the rage-creating trends of life. Alcohol and drugs, including marihuana, are easy, but ineffective, ways of doing so. A major overlooked question is “Why? What is our culture doing to make people, beginning in their early puberty, to want to “turn off” rather than eagerly engage in a productive life?” Even those who are well off? And what can we do about it? Before Birth